STUDI KOMPARATIF KELAYAKAN USAHATANI PAKCOY (BRASSICA RAPA SUBSP. CHINENSIS) SECARA HIDROPONIK DAN KONVENSIONAL - Salsabila Kadir; Supriyo Imran; Irwan Bempah (Universitas Wahid Hasyim, 2025)
Pak choy farming is the organized cultivation of bok choy plants to produce economically valuable agricultural products. This study aims to determine the current state of hydroponic and conventional bok choy cultivation techniques and to compare the feasibility of hydroponic and conventional bok choy farming. A total of 18 bok choy farmers were interviewed. The analysis used in this study was the R/C Ratio and B/C Ratio. The results indicate that both cultivation methods are feasible because they have R/C and B/C ratios above 1. The hydroponic method offers advantages in land use efficiency and environmental control, while the conventional method is more cost-efficient due to lower costs. Each method presents its own challenges, both technically and financially. Therefore, the choice of cultivation method is tailored to the conditions and capabilities of the farmer, as well as the objectives of the farming business.